Stop, look, listen: the need for philosophical phenomenological perspectives on auditory verbal hallucinations - McCarthy-Jones, Simon; Krueger, Joel; Larøi, Frank; Broome, Matthew R.; Fernyhough, Charles (Frontiers in Human Neuroscience, 2013)
One of the leading cognitive models of auditory verbal hallucinations (AVHs) proposes such experiences result from a disturbance in the process by which inner speech is attributed to the self. Research in this area has, however, proceeded in the absence of thorough cognitive and phenomenological investigations of the nature of inner speech, against which AVHs are implicitly or explicitly defined. In this paper we begin by introducing philosophical phenomenology and highlighting its relevance to AVHs, before briefly examining the evolving literature on the relation between inner experiences and AVHs. We then argue for the need for philosophical phenomenology (Phenomenology) and the traditional empirical methods of psychology for studying inner experience (phenomenology) to mutually inform each other to provide a richer and more nuanced picture of both inner experience and AVHs than either could on its own. A critical examination is undertaken of the leading model of AVHs derived from phenomenological philosophy, the ipseity disturbance model. From this we suggest issues that future work in this vein will need to consider, and examine how interdisciplinary methodologies may contribute to advances in our understanding of AVHs. Detailed suggestions are made for the direction and methodology of future work into AVHs, which we suggest should be undertaken in a context where phenomenology and physiology are both necessary, but neither sufficient.